(untitled) (Advances in Military Technology, 2022)
The article deals with applications of a DSP (Digital Signal Processor) in the MSK (FSK) demodulators. It describes simplified method of numerical processing of analytical signal. By simulation procedures it features achieved results and show possible applications.